29.9k views
1 vote
Plz Help!!!!!!!!!!!!!!!!!!!

Plz Help!!!!!!!!!!!!!!!!!!!-example-1
User Leon Xiong
by
4.7k points

1 Answer

3 votes

Answer:

x = 4

Explanation:

5[3(x + 4) - 2(1 - x)] - x - 25 = 14x + 65

Distribute by 3 and 2 inside the square bracket

5 [ 3x + 12 - 2 + 2x ] - x - 25 = 14x + 65

collect like terms inside the square bracket

5 (5x + 10) - x - 25 = 14x + 65 ← distribute the parenthesis by 5

25x + 50 - x - 25 = 14x + 65 ← collect like terms on left side

24x + 25 = 14x + 65 ( subtract 14x from both sides )

10x + 25 = 65 ( subtract 25 from both sides )

10x = 40 ( divide both sides by 10 )

x = 4




User Rodolfojcj
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.